Focus of attention in musical learning and music performance: a systematic review and discussion of focus instructions and outcome measures - Hohagen, Jesper; Immerz, Anna (Frontiers in Psychology, 2024)
The topic of attentional focus (FOA) in musical learning and performance has recently received increasing interest, as the growing number of empirical studies shows – inspired by the established FOA paradigm in sports by Wulf et al. (1998). The current systematical review aims at collecting, abstracting, and categorizing relevant data to show which kinds of FOA instructions were applied in experimental designs and what kinds of dependent variables were used to measure effects of FOA instruction on musical performance. The three main inclusion criteria in the selection process were experimental design, detailed descriptions of FOA instructions, and outcome measures (OM). Systematic search was conducted with a complex search term in four scientific databases in March 2023. For presenting and synthesizing results, we used data collection and an inductive-deductive data categorization (see five tables and review protocol). 15 studies with a total sample size of 401 participants were included out of 387 records initially identified. We collected 53 different FOA instruction citations from the 15 studies and classified them into 9 FOA subcategories of which the most applied were bodily focus (21%), sound focus (15%) and visual focus (14%). Selected studies used 63 OM that were abstracted to 10 different OM categories with expert ratings (27%) and acoustical analysis (22%) as most applied dependent variables. Data categorization and abstraction of additional study information show multiple combinations of FOA instructions, OM, participant’s instruments and expertise and musical tasks. Finally, studies show no consistent results of a superiority of either external or internal or otherwise different FOA considering positive effects on musical performance. Limitations of the review lie in the small study sample, possible criticism of applied eligibility criteria and subjectivity of data categorization. We propose a research agenda with a more exploratory approach that comprehensively and qualitatively examines the dimensions of musical goals to create a database that could provide a foundation for developing a music specific FOA model.